Therapeutic evaluation of intralesional measles, mumps and rubella vaccine in palmoplantar warts - K., Geetha (International Journal of Research in Dermatology, 2019)
Background: Warts are common viral infections of the skin caused by human papilloma virus. Most of the treatment modalities for common warts remain unsatisfactory. Immunotherapy has become one of the important therapeutic modality. This study was conducted to evaluate the efficacy of intralesional measles, mumps and rubella (MMR) vaccine immunotherapy in palmoplantar warts. Methods: 60 patients of various age groups and both sexes who have single or multiple palmoplantar warts not on any other concurrent systemic or topical therapy were randomly included for the study. Patients with other types of warts, signs of other infection, pregnancy, lactation and immunosuppression were excluded from the study. MMR Vaccine was injected intralesionally at 2 week intervals until complete clearance or for a maximum of 3 treatments. The outcome in terms of treatment relapse, recurrences and adverse effects were evaluated. Results: Only 54 patients completed the study and 41 (75.9%) of them showed complete response and 13 (24%) of them showed partial or no response. Conclusions: Intralesional MMR vaccine therapy appears to be a safe and effective treatment option with no significant adverse effects and low recurrence.